The Linkage Between Political Trust and the Quality of Government: An Analysis. Issue 9 (28th July 2016) - Khan, Haroon A.
ABSTRACT: Political trust has been declining not only in the developed world but also in developing and transitional countries. Political trust is necessary for the legitimacy of the government. Researchers explored the issues of political trust from many variables. However, the literature is not very clear in terms of the linkage between the quality of governance and political trust. Although some authors tried to incorporate government quality for explaining political trust, they failed to specify the linkage between them. This research will investigate the relationship between the quality of government and political trust in developing and transitional countries.